A history of Christian missions - Neill, Stephen, 1900-1984.; Chadwick, Owen. (Grand Rapids, MI William B Eerdmans Publishing Company, 1965)
"A History of Christian Missions traces the expansion of Christianity from its origins in the Middle East to Rome, the rest of Europe and the Colonies, and assesses its position as a major religious force worldwide. Many of the world's religions have not actively sought converts, largely because they have been too regional in character. Buddhism, Islam and Christianity, however, are the three chief exceptions to this and Christianity, in particular, has found a home in almost every country in the world. Professor Neill's excellent and authoritative survey examines centuries of missionary activity, beginning with Christ and working through the Crusades and the colonization of Asia and Africa up to the present day, concluding with a shrewd look ahead to what the future may hold for the Christian Church." -- Book cover.
PART ONE: A faith for the world -- The conquest of the Roman world, A.D. 100-500 -- The Dark Age, 500-1000 -- Early European expansion, 1000-1500 -- The Age of Discovery, 1500-1600 -- The Roman Catholic missions, 1600-1787 -- New beginnings in East and West, 1600-1800 -- PART TWO: Introduction -- New forces in Europe and America, 1792-1858 -- The heyday of Colonialism, 1858-1914 -- Rome, the orthodox, and the world, 1815-1914 -- From mission to church -- Yesterday and today, 1914 and after.
Includes bibliographical references (p. [479]-499) and index.
Keywords: Missions -- History; Missions -- History of doctrines; Church history